Pengaruh Suhu terhadap Nilai Analisis Proksimat pada Proses Karbonisasi Batubara untuk Carbon Riser di PT. XYZ, Kota Samarinda, Provinsi Kalimantan Timur - Guruh Tiedie Putra Prawira (Bandung Conference Series: Mining Engineering, 2021)
Abstract. Carbonriser or carbon riser is a material that serves to increase hardness in the iron and steel smelting process industry. This material is formed from compounds that have high carbon conditions. The main carbon material used as raw material for the carbonriser is green coke or petroleum coke. Green coke is a carbon residue obtained from the refining of heavier petroleum, in addition to green coke the carbon material that is widely used for carbonrisers is anthrachite coal. The increase in the value of solid carbon or fixed carbon is carried out through the carbonization process, carbonization is the process of converting organic material into carbon or carbon residue through the pyrolysis process. Pyrolysis is the thermal decomposition or decomposition of organic matter through a heating process with no or little oxygen, where the organic material will undergo a chemical structure breakdown into gas. Decomposition in limited air conditions, compounds that are easily lost (volatile) will become gases, so that the volatile matter content decreases and the FC content increases. The increase in FC value is also influenced by the reduced water content. There are several tests carried out to determine the quality of coal including proximate analysis (Inherent Moisture, Ash, Volatile Matter, Fixed Carbon and total sulfur. From the test results obtained the average value of the sample inherent moisture 3.61%, ash 8.9%, volatile matter 8.2%, fixed carbon 79.27% ​​and total sulfur 0.2%, for coal at a temperature of 800-830 Inherent moisture 3.7%, ash 7.8%, volatile matter 9.3%, fixed carbon 79.09%, total sulfur 0.2%, for coal at heating process temperature 831-860. Inherent moisture 3.77%, ash 8.08%, volatile matter 8.8%, fixed carbon 79.3%, total sulfur 0.21%, for coal at heating temperature 861-890. Inherent moisture 3.4%, ash 8.2 % … Abstrak. Carbonriser atau carbon riser adalah material yang berfungsi untuk meningkatkan kekerasan pada industri proses peleburan besi dan baja. Material ini terbentuk dari senyawa yang memiliki kondisi karbon tinggi. Material karbon utama yang digunakan sebagai bahan baku carbonriser yaitu green coke atau petroleum coke. Green coke adalah residu karbon yang diperoleh dari penyulingan minyak bumi yang lebih berat, selain green coke material karbon yang banyak digunakan untuk karbonriser adalah batubara antrachite. Peningkatan nilai karbon padat atau fix carbon dilakukan melalui proses karbonisasi, karbonisasi merupakan proses konversi material organik menjadi karbon atau residu karbon melalui proses pirolisis. Pirolosis adalah penguraian atau dekomposisi termal bahan organic melalui proses pemanasan tanapa atau sedikit oksigen,dimana material organic akan mengalami pemecahan struktur kimia menjadi gas. Dekomposisi pada kondisi udara terbatas, senyawa yang mudah hilang (zat terbang) akan menjadi gas, sehingga kadar zat terbang berkurang dan kadar FC akan meningkat. Peningkatan nilai FC juga dipengaruhi oleh berkurangnya kadar air. Ada beberapa pengujian yang dilakukan untuk mengetahui kualitas batubara diantaranya analisis proksimat (Inherent Moisture, Ash, Volatile Matter, Fixed Carbon dan total sulfur. Dari hasil pengujian didapat nilai rata-rata sampel inherent moisture 3.61%, ash 8.9%, volatile matter 8.2%, fixed carbon 79.27% dan total sulfur 0,2%, untuk batubara pada proses pemanasan suhu 800-830 Inherent moisture 3.7%, ash 7.8%, volatile matter 9.3%, fixed carbon 79.09%, total sulfur 0,2%, untuk batubara pada proses pemanasan suhu 831-860. Inherent moisture 3.77%, ash 8.08%, volatile matter 8.8%, fixed carbon 79.3%, total sulfur 0,21%,untuk batubara pada proses pemanasan suhu 861-890 . Inherent moisture 3.4%, ash 8.2%, …